A numerical model for nonlinear large deformation dynamic analysis of unsaturated porous media including hydraulic hysteresis. (September 2015) - Shahbodagh-Khan, B.; Khalili, N.; Alipour Esgandani, G.
Abstract: A numerical model based on the theory of mixtures is proposed for the nonlinear dynamic analysis of flow and deformation in unsaturated porous media. Starting from the conservation laws, the governing differential equations and the finite element incremental approximations suitable for nonlinear large deformation static and dynamic analyses are derived within the updated Lagrangian framework. The coupling between solid and fluid phases is enforced according to the effective stress principle taking suction dependency of the effective stress parameter into account. The effect of hydraulic hysteresis on the effective stress parameter and soil water characteristic curve is also taken into account. The application of the approach is demonstrated through numerical analyses of several fundamental nonlinear problems and the results are compared to the relevant analytical solutions. The effects of suction, large deformations and hydraulic hysteresis on static and dynamic response of unsaturated soils are particularly emphasized.